Optochemical nanosensors - Cusano, Andrea (Boca Raton, FL : Taylor & Francis, 2012)
'This book provides an overview of the state-of-the-art in optical and chemical nanosensors for industrial, environmental, diagnostic, security, and medical applications. It summarizes the various types and developments in optical and chemical sensor technology and then explains how the integration of optical/chemical sensors and nanomaterials creates new opportunities. The text also reviews optochemical sensors, starting from the basics in optoelectronics and concluding with the principles of operation at the basis of optochemical devices. The authors offer insight into future trends in this growing field and present a range of applications in the fields of medicine, security, and bioterrorism'--
Part 1 Basics -- Fundamentals of photonics / Brian Culshaw, Jose Miguel L{u2BF0}ez-Higuera -- Fundamentals of optical chemical sensors / Francesco Baldini, Ambra Giannetti, Cosimo Trono -- Optical chemical sensors: a look back / Dorota Wencel, Colette McDonagh -- Part 2 Research Advances -- Photoluminescent nanosensors / Mike McShane -- Cantilever-based sensors / Maria Tenje ... [et. al] -- Nanostructures surface plasmon resonance sensors / Mikael Scedendahl, Si Chen, Mikael Kl -- Fiber-optic nanosensors / Carlos R. Zamarre ... [et. al] -- Lab on fiber technology and related devices / Andrea Cusano ... [et. al] -- Micro/nanofibers for biochemical sensing / Joel Villatoro -- Optofluidic sensors / Romeo Bernini -- Lab-on-chip nanostructures sensors for chemical and biological applications / Luca De Stefano ... [et. al] -- Photonic crystals as valuable technological platform for chemical and biological nanosensors / Valery Konopsky, Elena Alieva -- Nano-materials and nano-structures for chemical and biological optical sensors / Ignacio Del Villar ... [et. al] -- Linar and nonlinear spectroscopy at nano scale / Anna Chiara De Luca ... [et. al] -- Plasmonic nanostructures and nano-antennas for sensing / Anuj Dhawan, Tuan Vo-Dinh -- Overcoming mass-transport limitations with optofluidic plasmonic biosensors and particle trapping / Hatice Altug ... [et. al] -- Optical micro-ring resonators for chemical vapor sensing / Yuze Sun, Xudong Fan -- Part 3 Applications -- Nano-optical sensors for the detection of bioterrorist threats / Vinad Kumar Khanna -- Nano-optical sensors for food safety and security / Euiwon Bae, Arun K. Bhunia -- Multifunctional fiber optic nanosensors for environmental monitoring / Alessio Crescitelli ... [et. al] -- Nano-optical sensors for virology / Sathish Sankar ... [et. al] -- Nano-optical sensors for explosive detection / Paul B. Ruffin, Stuart (Shizhuo) Yin.
Includes bibliographical references and index.
Keywords: Chemical detectors; Optical detectors; Nanoelectromechanical systems; Biosensors